The Effect of B-Cell Lymphoma 2 and BCL2-Associated X Polymorphisms on the Survival of Acute Lymphoblastic Leukemia Patients: Application of Frailty Survival Models - Navideh Nikmohammadi; Parvin Sarbakhsh; Mozgan Moazami Goudarzi; Mehdi Talebi; Majid Farshdousti-Hagh; Jamileh Malakouti; Neda Gilani (Tehran University of Medical Sciences, 2022)
Background: B-cell lymphoma 2 (BCL-2) and BCL-2 associated X (BAX) polymorphisms are important in the apoptosis process, response to treatment and survival in Acute Lymphoblastic Leukemia (ALL) patients. We aimed to investigate the effect of these genes with other predictors corresponding to the survival of ALL patients with an appropriate frailty survival model. Methods: Our study was performed in 2020 on sixty-two cases of childhood aged 3-16 (year) with ALL disease who were selected by convenience sampling from the two hospitals of Tabriz, Iran. RFLPPCR method was used for genotyping the promoter region of the BAX and BCL-2 genes. We used different frailty survival models, to control heterogeneity between individuals due to unmeasured factors affecting their survival. All analyses were implemented using Stata 16. Results:  Based on the result of log-logistic model along with frailty gamma, the proportional odds (standard error) of survival for a CC allele of BCL-2 patient compared to a AA allele patient were 6.0 (1.47); P<0.001 and for a AC of BCL-2 allele patient were 0.57 (1.23); P=0.009. Patients with AG allele of BAX had 2.05 (1.26) times greater odds of surviving than a AA allele patient (P=0.003). The odds of survival of patients with abnormal white blood cell (WBC) were 92% less than normal WBC (P<0.001). Conclusion: With controlling unmeasured factors affecting, the BCL-2 and BAX genes promoter polymorphism are effective in the survival rates for ALL.